Peningkatan Kompetensi Guru Bahasa Inggris melalui Pelatihan Metode Pembelajaran Berbasis Teknologi dan Manajemen Kelas di Sulawesi Selatan - Annisa Shofa Tsuraya; Nur Aliyah Nur; Muhammad Syahruddin Nawir; Indah Fadhilah Rahman; Sitti Nurpahmi (KHIDMAH: Jurnal Pengabdian Masyarakat, 2023)
The independent learning policy by the Ministry of Education and Culture, which was followed by the birth of Reform Madrasah, requires teachers to have 21st Century learning competencies, one of which is skills in using IT in learning. In line with that, the ability to manage student-centered classes is very important so that the stigma of learning that is still teacher-centered is no longer often heard. This community service activity aims to improve the competency of Madrasah Tsanawiyah English teachers through training in technology-based learning methods to be implemented in both online and offline learning, through classroom management training to be able to create a fun and student-centered teaching and learning process, and through preparation assistance learning planning and evaluation in South Sulawesi to be able to create a well-planned and measurable learning process. The method used in this training is training by applying the CBR (Community Based Research) model approach. The training was carried out in four stages, namely laying the foundation, planning, collecting and analyzing data (gathering and analyzing information), and following up (action on finding). Participants in this activity were 2 cities and 1 district in South Sulawesi Province including Palopo City, Makassar City and Gowa Regency with a total of 40 teachers from each city and district. The process of selecting training participants is representative of the selected schools on the recommendation of the local City and District Ministry of Religion offices. The results of this training show that the competency of Madrasah Tsanawiyah English teachers increases through training in technology-based learning methods to be implemented in both online and offline learning, through classroom management training to be able to create a fun and student-centered teaching and learning process, and through preparation assistance learning planning and evaluation in South Sulawesi to be able to create a well-planned and measurable learning process.